Indonesian Grammatical Interference in Translating Relative Clauses in Japanese Comic Strips - Puspitosari, Dwi; Setiawati, Ai Sumirah (Universitas Pendidikan Indonesia (Indonesia University of Education), 2024)
Bilingual communication, like translation, generates linguistic events due to interaction with two or more languages. The emergence of interference is one of the consequences of language contact. This study investigates the impact of Indonesian grammar on the translation of relative clauses in Japanese comic strips to examine the types of grammatical errors. This study also analyzes the morphological interference and syntactic interference at the phrase level as a result of the respondent’s translation and investigates the causes, as well as discovers the respondent’s difficulties and strategies during the translation process, particularly relative clauses in Japanese comic strips. A qualitative descriptive approach was used in this study, which data was collected by recording and analyzing the results of a mid-semester exam on comic strip translation for 56 students enrolled in a Japanese-Indonesian translation and interpreting (Honyaku-Tsuyaku) course in their third year. All respondents are proficient in JF Standard Japanese at the B1 level. Google Form questionnaires were distributed to ascertain the respondents’ difficulties and strategies when translating relative clauses. The findings of this study showed that language interference errors are the most prevalent, followed by errors involving word deletions, word additions, incorrect formation of sentence elements, and incorrect placement of components. Thirty translation results were Global Errors, and twenty-six were Local Errors regarding error severity. The results of the questionnaire found that the most significant difficulty was determining the part that is generalizing, determining the order of the translated parts, translating the particle that connects the generalization clause, determining the Subject-Predicate-Object-Description in the sentence, and when translating the demonstrative word that follows the generalization part consecutively.